2015
DOI: 10.1103/physrevd.92.064045
|View full text |Cite|
|
Sign up to set email alerts
|

Earth-moon Lagrangian points as a test bed for general relativity and effective field theories of gravity

Abstract: We first analyse the restricted four-body problem consisting of the Earth, the Moon and the Sun as the primaries and a spacecraft as the planetoid. This scheme allows us to take into account the solar perturbation in the description of the motion of a spacecraft in the vicinity of the stable Earth-Moon libration points L 4 and L 5 both in the classical regime and in the context of effective field theories of gravity. A vehicle initially placed at L 4 or L 5 will not remain near the respective points. In partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…However, by patiently applying the time derivative operator four times to Eq. (4.3) (see Appendix A for details) the fourth time derivatives x (4) r are found to solve a linear system of ordinary differential equations of the form…”
Section: Linear System Of Ordinary Differential Equations Associamentioning
confidence: 99%
“…However, by patiently applying the time derivative operator four times to Eq. (4.3) (see Appendix A for details) the fourth time derivatives x (4) r are found to solve a linear system of ordinary differential equations of the form…”
Section: Linear System Of Ordinary Differential Equations Associamentioning
confidence: 99%
“…Considering that the distance between the two Lagrangian points L 1 and L 2 is y 1 + y 2 3 Ă— 10 9 m, and assuming an impact parameter b of the order of the Earth's radius R ⊕ 6.4 Ă— 10 6 m, for the propagation time of Eq. (8) we obtain: (9) where the contribution of each term has been highlighted. If we consider a round trip travel for the propagation time, the smaller contribution of the gravitomagnetic field cancels out when we consider the propagation on the same side of the Earth, and the quadrupole effect can be extracted after modelling the Shapiro delay and the larger effect of the propagation time in the flat spacetime of Minkowski.…”
Section: Time Delays For a Configuration Where Emitter And Receiver Amentioning
confidence: 99%
“…The deflection angle for a light beam evolving in Kerr geometry is given by [4] 15) where the first term is the same as in Schwarzschild spacetime, the second one is due to the oblateness of the body of mass M , whereas the last one is related to angular momentum and hence it represents a gravitomagnetic effect. From Eqs.…”
Section: Quantum Corrected Time Delaymentioning
confidence: 99%
“…(3.12), (3.13), and Unfortunately this deviation from the underlying classical theory has no chance to be tested, unlike, for example, the effects some of us predicted in Refs. [10,11,14,15], where it is shown that Earth-Moon Lagrangian points are expected to undergo a displacement of the order of few millimetres from their classical position. Furthermore, we have proved that the result reported in Eq.…”
Section: Concluding Remarks and Open Problemsmentioning
confidence: 99%